Generalized Net Model of a Body Temperature Data Logger Embedded System - Lenko Erbakanov; Krassimir Atanassov; Sotir Sotirov (International Journal Bioautomation, 2015)
This paper represents a prototype embedded system, intended for measuring, gathering and transmitting the obtained data of the temperature of the skin and the ambient air. The system is designed to collect data in relatively short intervals, for fairly long periods of time. The skin temperature measurements are performed using an infrared temperature sensor. Some experimental results are also presented.